New Trends in Information and Communications Technology Applications : 4th International Conference, NTICT 2020, Baghdad, Iraq, June 15, 2020 Proceedings - Al-mamory, Safaa O.; Sahib ,Mouayad A.; Hasan, Haitham; Oreku, George; Nayl, Thaker M.; AL-Dhaibani, Jaafar A. (Cham, Switzerland : Springer, 2020)
This book constitutes the refereed proceedings of the Third International Conference on New Trends in Information and Communications Technology Applications, NTICT 2018, held in Baghdad, Iraq, in October 2018. The 18 papers presented were carefully reviewed and selected from 86 submissions. The papers are organized in topical sections, namely: Computer networks; system and network security; machine learning; intelligent control system; communication applications; computer vision; and e-learning.
Computer Networks -- System and Network Security -- Machine Learning -- Intelligent Control System -- Communication Applications -- Computer Vision -- E-learning.
Keywords: Computer organization; Data mining